Managing from the Boundary: The Effective Leadership of Self-Managing Work Teams - Druskat, Vanessa Urch; Wheeler, Jane V. (Academy of Management Journal, 2003)
We used in-depth critical incident interviews with the external leaders of self-managing work teams and their team members, and interviews and surveys provided by managers, to understand how effective leader behaviors and strategies unfold over time. Content analyses of the data produced a process model showing that effective external leaders move back and forth across boundaries to build relationships, scout necessary information, persuade their teams and outside constituents to support one another, and empower their teams to achieve success.